Combination of Atorvastatin–Endurance Training Has Positive Effect on Apoptosis and Protein Expression of SDF-1α/CXCR4 Axis after Myocardial Infarction in Rat’s Heart Tissue - Azamian Jazi1, Akbar; Abdi2*, Hadi; Shamsaei3, Nabi; Khaksari4, Mehdi (Shahroud Journal of Medical Sciences, 2017)
Background: It is a well-known fact that both statins and exercise have beneficial effects in preventing cardiovascular disease; however, no information is available about their combinatorial effect on the cardiac cell apoptosis and protein expression of SDF-1α/CXCR4 after myocardial infarction (MI). This study aimed to evaluate the combined effect of endurance training and atorvastatin on the apoptosis and protein expression of SDF-1α/CXCR4 in the cardiac tissue of rats following MI.Methods: In total, 30 rats (8–10 weeks old, weighing 220–240 g) were randomly divided into five groups. Myocardial infarction was induced by subcutaneous injection of isoprenaline (150 mg/kg) in 2 consecutive days. Drug and training intervention was initiated 2 days after infarction and was continued for 4 weeks. To assess apoptotis and protein expression of SDF-1α/CXCR4 axis, Tunnel and IHC staining were performed, respectively.Results: The combination of endurance exercise and atorvastatin significantly reduced the number of apoptotic cells and increased the protein expression of SDF-1α compared with the other groups (P<0.001). Moreover, this combination significantly increased the protein expression of CXCR4 compared with the control and sham groups (P<0.001) and with the atorvastatin group (P<0.05). Endurance exercise training and atorvastatin, individually induced a significant decrease in the apoptotic cell count (P<0.001) and nonsignificant increase in the protein expression of SDF-1α /CXCR4, compared with the control group.Conclusions: Results of this study revealed that the combined effects of training and atorvastatin are more efficient in reducing the apoptosis and upregulation of SDF-1α/CXCR4 than exercise or atorvastatin alone.